Theoretical aspects of semantics-based language implementation = Teoretiske aspekter af semantik-baseret sprog-implementation - Nielson, Flemming, 1955- (DAIMI. Aarhus University. Computer Science Dept. ;, 1990)
Abstract: "The research summarised here concerns theoretical aspects involved in the implementation of programming languages directly from a description of their semantics. This involves a study of the subtasks abstract interpretation (a framework for program analysis), code generation and program transformation and the main aim has been to ensure the correctness of these subtasks."